The Smart City Conundrum for Social Justice: Youth Perspectives on Digital Technologies and Urban Transformations. Issue 2 (3rd March 2020) - Masucci, Michele; Pearsall, Hamil; Wiig, Alan
Abstract : This article employs a social justice framing to examine youth perspectives of the smart city. We examine how youth understand the impact of digital technologies on urban transformations and whether their technology skills and digital literacy give them a sense of ownership over the future of their city. Research was conducted within the context of a six-week summer educational program involving seventy-nine youth of color from public high schools in Philadelphia, Pennsylvania. The program mixed digital skill building with urban fieldwork to prototype solutions to long-standing urban problems: the sort of problems that smart city policies also seek to change. Our research points to a conundrum for youth. Although they embraced technological innovations, they indicated that digital technologies failed to serve the public or address pressing concerns they identified as problematic within the city: crime, drugs, and homelessness. Instead, in their view, digital technologies delivered the most benefit to private spaces in the home and workplace. Furthermore, the youth did not envision that emergent technologies would improve their neighborhoods or communities but only their employment prospects. This research suggests that the emergent smart city is reproducing actual as well as perceived urban inequities: Wealthy residential neighborhoods and spaces of the new economy become "smart, " but much of the city remains left behind. These patterns create a paradox for youth who invest in digital skills while remaining on the margins of technology-driven, smart urban change. Key Words: digital divide, Philadelphia, smart city, social justice, youth.